Enhancing the intercultural effectiveness of exchange programs: formal and non-formal educational interventions - Almeida, Joana
This paper examines how the addition of intercultural interventions carried out throughout European credit-bearing exchange programmes can enhance sojourners’ development of intercultural competencies, and it explores how both formal and non-formal pedagogical interventions may be designed and implemented. Such interventions were conducted at a Portuguese university with 31 sojourners throughout one academic year, and their impact was assessed using a mixed methods research design. Sojourners included incoming students of the exchange programmes Campus Europae and Erasmus, as well as highly skilled immigrants. Findings confirm the positive impact of interventions on the development of intercultural competencies and, in turn, their contribution to internationalisation efforts. Implications for further research suggest a need to increase interventions and to develop a systematic approach for fostering intercultural competencies throughout the study abroad cycle.